The Birth of Endowiki, An Italian Online Platform for Continuous Medical Education In Endocrinology - Attanasio Roberto; Gualano Luca; Misischi Irene; Caprioli Silvia; Papini Enrico; Toscano Vincenzo; Garofalo Piernicola (Journal of Medical Informatics and Decision Making, 2018)
Background Conventional tools for medical education are burdened by many drawbacks. Textbooks become rapidly outdated, meeting attendance is expensive, and results reported in journals are not easily suitable for clinical practice. Uptodate and Endotext are excellent online tools, but they have been developed for a clinical context far different from that of our country. Methodology Italian Association of Clinical Endocrinologists (AME) charged a task force aiming to develop an educational tool specifically tailored for Italian clinical endocrinologists. Required characteristics were clinical approach, modularity, continuous updating, full online availability (even by mobile devices), open sections and sections for registered members only, opportunity for individualization, indexing and search engine to facilitate browsing. Starting from an open-source platform, Joomla, several changes were implemented. Results Three editors, 2 central editorial secretaries, 30 section coordinators and over 350 authors have been involved in the writing of 21 different sections covering all fields of endocrine and metabolic diseases. The access to Endowiki is free for AME members and is fully open in sections for patients. All readers are requested to serve as referee, pointing to mistakes and need for revision. The system is attended daily by a mean of 250 individuals. Conclusions Endowiki stands alone as an opportunity for medical education in Italy. The big challenges will be the continuous updating and the link to the national certified system for CME.
Keywords: online platform